Ethnotheology of Kosu Dance: Reconstruction of the Meaning of Syukur Amarasi Within the Framework of Multicultural Christian Religious Education - Febirina Norliantyn Atty (PT FORMOSA CENDEKIA GLOBAL, 2026)
This study examines the Kosu Dance as a cultural expression of the Amarasi tribe in Kupang Regency, East Nusa Tenggara, from an ethnoteological perspective. The Kosu Dance is a traditional dance performed in the context of wedding ceremonies, where community members both family and invited guests voluntarily and with sincere hearts place money on the heads of the bride and groom as a form of blessing, support, and prayer for the couple embarking on a new family life. This study aims to identify the theological meanings embedded in this voluntary giving practice, as well as to reconstruct the meanings of gratitude and generosity manifested in the Kosu Dance within the framework of Multicultural Christian Religious Education (PAK).